2013
DOI: 10.5251/abjna.2013.4.1.6.13
|View full text |Cite
|
Sign up to set email alerts
|

Performance and erythrocyte osmotic membrane stability of laying Japanese Quails (Coturnix coturnix japanica) fed varying dietary protein levels in a hot-humid tropics

Abstract: A thirteen week feeding trial was conducted to determine the effects of feeding varying levels of dietary protein on productive performance, egg quality traits, erythrocyte osmotic fragility and haematological parameters using 195 six weeks old laying quails. The birds were randomly allocated to five dietary treatment groups of thirty nine (39) birds each, and were further replicated three times with thirteen (13) birds per replicate. They were fed five experimental diets containing 17, 18, 19, 20 or 21%CP. Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 12 publications
3
13
1
Order By: Relevance
“…It also disagree with [42,43] which reported that male geese and budgerigars were shown to have higher values in most of their blood parameters relative to their female counterparts. Sex had significant (P<.05) difference on some of the heamatological parameters which agrees with those reported previously by several authors [37,49,52,53,54,55] which reported that sex has significant influence on Hb, RBC and MCHC with females having higher significant values than Males. The results obtained in this study for Hb disagrees with the observation of [39,51] which observed no significant difference in both sexes of the quails.…”
Section: Effect Of Sex On the Haematological Parameters Of Japanese Qsupporting
confidence: 91%
“…It also disagree with [42,43] which reported that male geese and budgerigars were shown to have higher values in most of their blood parameters relative to their female counterparts. Sex had significant (P<.05) difference on some of the heamatological parameters which agrees with those reported previously by several authors [37,49,52,53,54,55] which reported that sex has significant influence on Hb, RBC and MCHC with females having higher significant values than Males. The results obtained in this study for Hb disagrees with the observation of [39,51] which observed no significant difference in both sexes of the quails.…”
Section: Effect Of Sex On the Haematological Parameters Of Japanese Qsupporting
confidence: 91%
“…This weight was not different from that reported by Bidura et al (2014) that egg weight of Lohmann brown at the age of 42-50 weeks was 58.12 g. Factors affecting egg weight are protein consumption (Tuleun & Adenkola, 2013) and age (Tserveni-Goussi & Fortomaris, 2011). According to Leeson & Summers (2005), protein and amino acids (especially methionine) are nutrients that have important roles in controlling of eggs size.…”
Section: Laying Hens Performancementioning
confidence: 50%
“…These results are in agreement with those of Dos Santos et al (2016), who did not find any significant effect on feed intake or egg production of quails fed 16 or 20% CP. In addition, previous observations in Japanese quails determined that increasing dietary CP from 17 to 20% (Tuleun et al, 2013) or from 15 to 20% (Muhammad et al, 2016) did not affect egg production, but did improve feed conversion ratio. A recent study showed that increasing dietary CP from 18 to 24% did not affect egg production, egg weight, or feed conversion ratio in Japanese quails .…”
Section: Production Performancementioning
confidence: 88%